Per un ritorno del progetto al centro - Alessandra Capuano (Ardeth, 2020)
The contribution focuses on the problematic condition of architects within the Italian academic environment, trying to figure out parallelisms between architectural production and cultural production. The peculiarity of architecture, which is located between hard and soft sciences, produces a series of conflicts at the intersection between the field of pure research and that of research by design. This situation occurs in a specific moment in which architecture is much more valued as the result of a process instead of a creative, cultural and artisanal gesture. Meanwhile, in the academic field, the same focus on the product is oriented to the evaluation of real scientific contributions, with scarce attention to the value and the role of architectural design and research by design. In addition to this, the difficulty for researchers to develop a professional experience seems to anticipate a complete division between the world of architects and teachers of architecture. This mechanism, favoured by the evaluation system adopted by the Italian Ministry, necessitates of a profound reflection on the condition of architectural production, to redefine the reciprocal relationships between theory and practice, profession and education.